Microvariation in the resolution of pronominal subjects in romance: European Portuguese vs. Italian - Fiéis, Alexandra (2022)
The present study investigates how adult native speakers of two null subject Romance languages, European Portuguese (EP) and Italian,interpretnull and overt pronominal subjectsin intrasentential contexts. Participants were 30speakers of EP and 30of Italian. Each language group was administered two multiple-choicetasks (speeded and untimed), whichcrossedthe following variables: 'animacy of the matrix object'([+ human]vs. [-human]) and 'type of pronominal embedded subject'(overt vs. null). Our results showthat there is microvariation in the resolution of overt pronominal subjects in EP and in Italian: the position of the antecedent is the most relevant factor in EP, whereas, in Italian, the animacy of the antecedent is the preponderant factor. Moreover,our results reveal that the resolution of null subjects is an area of microvariation: the bias for subject antecedents is weaker in Italian than in EP. Possible reasons for the observed microvariation are discussed in detail